Investigation of Vitamins, Glutathione and Stress Biomarkers in Blood Serum of Patients with Breast Cancer - Awla Ibraim, Awat Hamad; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (Sakarya University, 2023)
Breast cancer is a genetic disease caused by the accumulation of mutations in neoplastic cells and is responsible for the highest morbidity and mortality. In this study, blood serum samples from 45 breast cancer patients and 32 healthy individuals (control group) were used. The amounts of vitamins (A, E, ?-carotene, C, B1, B2, B3, B5, B6, B9 and B12), glutathione (GSH, GSSG) stress biomarkers (4-HNE, MDA) were determined by HPLC. A significant difference was found between the breast cancer patients and the control group in terms of age and body mass index (BMI) (p<0.05). In the breast cancer group, fat-soluble vitamins, A, E and ?-carotene decreasing highly significant (p<0.001), decreasing water-soluble vitamins was found to be significant (p<0.05). No statistically significant difference was observed between the groups that received and did not receive treatment except vitamin B2 (p> 0.05) with in the cancer patients. Likewise, no significant difference was observed between the serum vitamin levels of breast cancer patients who breastfeed and not breastfeed, except for vitamins B2 and B3 (p>0.05). A high level of significant difference was observed between GSH, GSSG, MDA and 4-HNE in the breast cancer patient and control groups (p<0.001). There was no significant difference found in GSSG, MDA and HNE values according to the treatment status of breast cancer patients, on the other hand, a significant difference was observed in GSH and GSH/GSSG values (p<0.05). While there was no significant difference in GSH, GSSG, MDA and 4-HNE values according to the breastfeeding status of patients, a significant difference was observed in GSH/GSSG values (p<0.05). © 2023, Sakarya University. All rights reserved.
Keywords: 4-hydroxy neoneal; Breast cancer; Malondialdehyde; Oxidised glutathione; Reduced glutathione; Vitamins